Creation of tambaqui associated to hydropony in a water recycling system (Research, Society and Development, 2020)
Aquaponics is a form of food production that involves the integration between aquaculture and hydroponics into a closed water and nutrient recirculation system. This study evaluated the growth of tambaqui (Colossoma macropomum) associated with hydroponics during a period of 110 days was evaluated. Satisfactory values were obtained to weight gain, feed conversion and fish survival, which one presented a length and final weight respectively, 15.5 ± 1.09 cm, and 67.78 ± 13.86 g, at the fish density of 50.m-3. Total feed intake was 7.0 kg, the feed conversion was 1.1 and the final biomass was 3.86 kg m-3. The survival, 100%. The quality of the water was kept within the standards for the good development of tambaqui. However, in relation to the plant, during the observed period (40 days) the amount of nutrients produced from the waste water from the nursery stage was not satisfactory for lettuce development. In the conditions of the present study, it is concluded that the aquaponics system can ensure a sustainable development in the rearing of tambaqui in the stages of reise and rearing in relation to water quality and performance, however, in relation to lettuce a greater contribution of nutrients should be supplemented to ensure a good development of the plants.